Enterprise Architecture Maturity Assessment of Research Laboratory Management Systems - Ahmad Siar Sadr; Roohollah Tavallaee; Mohammad Ali Afshar Kazemi (Tehran University of Medical Sciences, 2022)
Background and Aim: Enterprise Architecture based on laboratory needs, and by using of the commons of valid and existing enterprise architecture frameworks, leads to the aligns of needs with organizational strategies and goals and information technology infrastructure. The aim of this study was the investigation of the effect of enterprise architecture model implementation on laboratory information management systems. Materials and Methods: In this quantitative study in 2020, proposed enterprise architecture model which was based on the compilation of Zachman and service-oriented architecture models was investigated by the maturity of enterprise architecture at Sharif University. The statistical community of this study was 100 laboratory specialists based on Morgan sample determination table CCM (Capacity Maturity Model), which was designed based on the Likert spectrum, was used as a questionnaire assessment tool. For data analysis, descriptive indicators such as frequency, percentage and one-sample t-test to compare the mean in SPSS software was used. Results: Assessing the maturity of enterprise architecture including four areas of IT (Information Technology) planning and organization, IT development and implementation, IT service and support, and IT monitoring and evaluation. Among the various dimensions of enterprise architecture maturity, the lowest average was related to the field of monitoring and evaluation and the highest average was related to the field of service and support. Dimensions in terms of status were: service and support dimension, planning and organizing dimension, development and implementation dimension, monitoring and evaluation dimension, respectively. The test results were significantly different in the areas related to the maturity of enterprise architecture, including the planning and organization areas, development and implementation, service and support (P<0.0001).  There was no significant difference in monitoring and evaluation. Conclusion: The use of enterprise architecture specific to laboratory management systems causes the optimal use of resources and ease of interaction. Evaluation of the implementation of the proposed architectural framework in the laboratory environment showed that the proposed model has matured in the three areas of planning and organization, development and implementation, service and support. In order to improve the maturity of enterprise architecture, more attention should be paid to the field of monitoring and evaluation and the reform program should start from this field.